HR Approaches to Diversity Management : Examining the Role of Age, Gender and Nationality in Czech Companies - Kudii, Yuliia (2025)
This thesis aims to investigate the strategies and practices employed by HR departments in Czech companies to manage diversity, with a particular focus on age, gender, and nationality. The study will explore how HR managers approach diversity in recruitment and workplace inclusion, examining the practical steps taken to address challenges and leverage the benefits associated with a diverse workforce. Through interviews with HR professionals, this research will identify challenges, D&I strategies, and the influence of diversity management on fostering a cohesive and inclusive work environment. The findings will provide qualitative insights and practical recommendations for enhancing diversity management practices in the Czech context.